Aprendizagem supersticiosa: um estudo na saúde pública durante a pandemia - Castro, Simone da Silva (2025)
Organizational learning is a fundamental factor, especially in the uncertain and insecure environment generated by a pandemic. This research reflects on superstitious learning, which occurs when the subjective learning experience is convincing, but the connections between actions and results are poorly specified. This study was conducted in the city of Barracão – PR, within the public health system, with healthcare professionals who worked during the Covid-19 pandemic. The objective was to understand the interference of superstitious learning in the organizational learning of the municipal public health system of Barracão – PR, in the face of the Covid-19 pandemic. A qualitative research approach was used, employing interviews, observation, and document analysis. Data analysis employed the interpretive textual analysis of Gil Flores (1994). The aim was to understand how superstitious learning interfered with organizational learning during the Covid-19 pandemic, considering that organizations need to understand the organizational learning of their institutions and that events like this pandemic are cyclical and others will likely occur in the future. This study identified that superstitious learning interferes with organizational learning in the municipal public health system of Barracão – PR, in the face of the Covid-19 pandemic. The analysis showed that its occurrence is associated with two central factors: beliefs and misinterpretations. Regarding beliefs, it is observed that they negatively impact both the psychological safety of individuals and the construction and sharing of tacit knowledge, fundamental elements for the organizational learning process. In turn, misinterpretations directly affect organizational routines and organizational memory, compromising efficiency and the consolidation of institutional practices. Two factors were identified as causes for the occurrence of superstitious learning: lack of time for decision-making and lack of a system for measuring indicators and results. The focus of actions was on execution and not on analysis; in the case of this study, the environment of uncertainty pressured managers to make decisions. Regarding the lack of a system for measuring indicators and results, it should be considered that, in the public sector, it is essential to assess whether objectives and goals are being achieved; if a tool for this purpose existed in the health system of Barracão – PR, it would be yet another barrier to avoid superstitious learning. Based on the results obtained in this thesis, managers can develop organizational strategies to avoid superstitious learning. It is suggested that research be continued in other areas of the public sector, investigating the relationship between individual and organizational learning and superstition.